Foster Parent Strategies to Support the Functional Adaptation of Foster Youth. Issue 3 (26th May 2016) - Semanchin Jones, Annette; Rittner, Barbara; Affronti, Melissa
Abstract : Individual interviews and focus groups with 35 experienced foster parents explored strategies that facilitate the functional adaptation of children transitioning into their care. Findings from this qualitative study suggest functional adaptation is enhanced by unconditional commitment by foster parents, "claiming" behaviors of foster children and parents, establishment of routines, support of birth family relationships, and advocacy for the youth across systems. Implications of this study support the vital role that foster parents have in helping children adapt to placement, and indicate that agencies can provide increased support for foster parents to better meet the needs of foster youth.